High sensitive dielectric filled Lamé mode mass sensor - Heidari, Amir (2013)
A new high performance mass sensor is designed and fabricated. The mass sensor is a single-crystal silicon squared resonator with dielectric filled capacitive excitation mechanism. The resonators were fabricated using the silicon-on-insulator MEMS process. In order to study the mass sensitivity of the fabricated resonator, a polyelectrolyte multilayer (PEM) is used to coat on the resonator surface. The resonator has the resonance frequency of 34.81 MHz, mass sensitivity of 105.4 μm2/ng. Experimental measurements of the mass sensitivities agree with theoretical predictions. The new developed mass sensor shows a high potential to be used in gas sensing and bio detection applications.